Pengembangan Media Pembelajaran Doratoon Berbasis PBL untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPA Kelas IV SD - Asyhari, Selvi Habibah; Hidayat, Hidayat (Jurnal Dirosah Islamiyah, 2024)
This research aims to develop a doratoon learning medium based on PBL on IPA subjects in grade IV SD. Students' learning interest in the learning process is an important role in learning. To ensure that learning goes smoothly, the student's interest in learning is crucial. We need an application of learning that supports the occurrence of such things and potentially student centers. One such learning model is the problem based learning model. Researchers are interested in raising a learning medium to attract student learning interest in the learning process. The type of research used is R&D (Research and Development). The model used in this research is the ADDIE development model. (Analysis, Design, Development, Implementation, Evaluation). Data collection with observations, interviews, spreadsheets and documentation studies. The results of the research showed that the media output after the revision obtained a 97.5% credibility percentage with the category “Very Worthy” and the material outcome after the review gained a 100% credibility percent with the categories “very worthy”. Thus, the development of doratoon learning media based on PBL on IPA subjects in grade IV SD is highly suitable for use by schools, teachers and students.